Collaborative software effort: activities in Japan and cooperation in Asia - Niibe, Yutaka (2003)
In this paper, we discuss the Free Software Movement in Japan and its counterparts around eastern Asia. The situation in these areas varies considerably, making it impossible to investigate and describe every case. For this reason, we begin by writing from the commondenominator viewpoint of the “Collaborative Software Effort”. We then describe in detail what is happening in Japan, giving typical examples and covering several major projects. Next, we briefly discuss cooperation in east Asia, which is just beginning, and future plans and hopes.